(untitled) (Jurnal Manajemen dan Kewirausahaan, 2015)
Marketers lately built strategies based on consumer communities exist in the market. Community that drew most of marketer’s attention was brand community. Brand community’s succession was influenced by consumer participation inside it, so that this article revealed variables which influenced consumer participation and consumer’s behaviors arose. This research took place through internet on Android virtual brand communities, those were online forums and Android virtual communities developed in Facebook. Data was analyzed with SEM (Structural Equation Modeling). The research found that there were significantly positive influenced whether of community identification or community satisfaction on consumer participation. Significantly positive influenced of consumer participation whether on WOM or brand image. It significantly negative influenced of consumer participation on switching intention.